Population attributable fractions for colorectal cancer and red and processed meats in Colombia - a macro-simulation study. (Colombia Medica, 2017)
Aim: to estimate the population attributable risk of consumption of red and processed meat for colorectal cancer in Colombia.Methods:  to model the expected incidence of colorectal cancer in the hypothetical situation of no red and processed meat consumption in Colombia, for the year 2010. A dynamic macrosimulation model, PREVENT 3.01, was used to integrate available cancer incidence, meat consumption prevalence and associated risk data and to evaluate the impact of eliminating red and processed meat from the Colombian diet on national colorectal cancer incidence.Results: Eliminating consumption of red meat altogether from the Colombian diet resulted in reductions in age-standardized colorectal cancer incidence, translating in reductions of 331 males (PAF 13%) and 297 female cases (PAF 10%). Eliminating processed meats had slightly stronger effects, with decreases of 362 males (PAF 14%) and 388 female cases (PAF 13%).Conclusions:  A substantial proportion of the burden of colorectal cancer in Colombia can be attributed to the consumption of red and processed meat.